Co-Determination, Efficiency, and Productivity - Felix R. FitzRoy; Kornelius Kraft (Institute for the Study of Labor (IZA), 2004)
We present the first panel estimates of the productivity effects of the unique German institution of parity, board-level co-determination. Although our data span two severe recessions when labour hoarding costs of co-determination are probably highest, and the panel is too short to capture the likely long run benefits in terms of human capital formation and job satisfaction, we find positive productivity effects of the 1976 extension to parity codetermination in large firms.
Keywords: J5; D2; L2; 330; co-determination; employee involvement; productivity; Mitbestimmung; Produktivität; Grossunternehmen; Schätzung; Deutschland